دراسة العلاقة بين القطب البيداغوجي و القطب السيكولوجي في المثلث الديداكتيكي في درس التربية البدنية و الرياضية - باباي, قيس; ناصري, محمدالشريف (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى الكشف عن العلاقة بين القطب البيداغوجي و القطب السيكولوجي في المثلث الديداكتيكي في حصة التربية البدنية و الرياضية في الطور الثانوي فاعتمدنا المنهج الوصفي للوصول إلى النتائج و قد صممنا استبيانا خصص لهذا الغرض متكون من 22 عبارة وقد تم التأكد من صدقه و ثباته، و موجه للتلاميذ حيث اخترنا عينة من ثانويات ولاية تقرت قدرت ب116 تلميذا و تلميذة من المستويات الثلاثة، و قد توصلت النتائج إلى وجود علاقة متوسطة ذات دلالة إحصائية بين القطبين البيداغوجي و السيكولوجي في المثلث الديداكتيكي في حصة التربية البدنية و الرياضية في الطور الثانوي مع عدم وجود فروق في مستوى القطب البيداغوجي ترجع للمتغير النوع، أما متغير المستوى الدراسي فلقد توصلنا إلى وجود فروق بين السنة أولى و السنة الثانية و الثالثة ،كما لم تكن هناك فروق في مستوى القطب السيكولوجي ترجع لمتغيري النوع و المستوى الدراسي . The study aimed to reveal the relationship between the pedagogical and the psychological poles in the didactic triangle in a secondary stage physical education and sports class. We shoes a sample of high schools in the state of Touggourt we designed a 22 expression question, 116 male and female students from the three levels were considered. The results showed that there was an intermediate relationship with statistical significance between pedagogical and psychological pole. With no differences in the level of the pedagogical pole, that is due to the gender variable. As for The academic level variable, we found that there are differences between the first year and the second and third year. There are also no differences in the level of the psychological pole because of the variables of gender and the education level.
في الطور الثانوي
مقال
Keywords: Didactic triangle, pedagogical pole, psychological pole, physical education and sports lesson, secondary phase